Fatal evolution of a huge right atrial free‐floating thrombus. Issue 2 (13th November 2013) - Bodian, Malick; Ba, Fatimata G.; Jobe, Modou; Ndiaye, Mouhamadou B.; Kane, Adama; Sarr, Simon A.; Mbaye, Alassane; Gaye, Abdou M.; Thiam, Ibou; Diao, Maboury; Sarr, Moustapha; Bâ, Serigne A.
Key Clinical Message Right atrial thrombus is a rare medical emergency that should be suspected in all cases of pulmonary embolism, and rapid action should be taken to ensure a timely, proper management.